The effect of maleic anhydride polyethylene on mechanical properties of pineapple leaf fibre reinforced polylactic acid composites - Siregar, Januar Parlaungan; Jaafar, Jamiluddin; Mat Rejab, Mohd. Ruzaimi; Tezara, C.; Choo, Chee Jie; Bachtiar, Dandi; Asmara, Y. P. (Springer, 2019)
The study of natural fiber composite in the field of materials has indeed sparked interest among many due to its essential biodegradability feature. As such, pineapple leaf fiber (PALF) is not only biodegradable, but also environmental friendly, as opposed to synthetic fiber. Hence, this paper investigates the effect of fiber loading, as well as the inclusion of maleic anhydride polyethylene (MAPE) to the mechanical properties of PALF reinforced polylactic acid composites. Therefore, untreated PALF with 0, 5, 10, and 15% of weight content ratio, as well as PALF at 10% weight ratio treated with 2, 4, and 6% of MAPE, had been prepared via roll mill mixing at 190 °C and followed by hot compression molding to prepare the specimen sheets. The results obtained from this study revealed that the tensile strength (TS) and the Young’s modulus were at their highest levels for untreated 10% PALF, while the impact and the flexure properties displayed a decrease as the content of fiber increased. Other than that, the inclusion of MAPE indicated that the tensile properties exhibited lower value compared to that of untreated. However, the flexural and the impact properties of composites increased with the presence of MAPE. As a conclusion, the study demonstrates that the mechanical properties depended on two major factors; (1) fiber loading, and (2) the compatibility between matrix polymer and fiber